Modelling intermediate care services as part of an integrated care pathway - Wilson, Nicola Ann (Health Policy and Systems Division, 2016)
This study explores the implications of implementing enhanced or redesigned intermediate care initiatives in the Western Cape of South Africa from the 2014/15 financial year onwards. Using a dynamic modelling methodology, we developed an empirical model of an integrated care system to explain the linkages, relationships and interactions among service components and analyse the implications of one of the proposed Healthcare 2030 policy interventions - intermediate care - on hospital admissions, waiting times and length of stay of all patients. We tested and compared a number of alternative intervention points using a simulation model parameterised with service component data from the Department of Health Information Systems. The findings from the study show the inconsistencies between the perceived structure and the available data from the respective service components that describe the resultant behavioural effects on an integrated care system, especially when care pathways cross organisational boundaries. The main managerial learning was around the existence and nature of organisational boundaries that require joint working and sharing of information. We conclude from the simulation results for the alternative scenarios tested that the implementation of enhanced or redesigned intermediate care initiatives can moderate the rate of growth in the demand for hospital services by reducing a percentage of hospital readmissions.